2010
DOI: 10.1089/pho.2010.2771
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photobiomodulation of Proliferation of Cells in Culture: A Review of Human and Animal Studies

Abstract: Findings from studies of cells in culture clearly demonstrate the ability of laser irradiation to modulate (typically stimulate) cellular proliferation. The relevance of some irradiation parameters remains occult and represents an important area for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 67 publications
5
50
0
18
Order By: Relevance
“…84 While a similar device and dosimetry were apparently used, lack of details on precise parameters makes it difficult to interpret these negative results. 85,86 This emphasizes the need to further understand PBM mechanisms that will aid in optimizing effective clinical protocols.…”
Section: Secondary Phasementioning
confidence: 99%
“…84 While a similar device and dosimetry were apparently used, lack of details on precise parameters makes it difficult to interpret these negative results. 85,86 This emphasizes the need to further understand PBM mechanisms that will aid in optimizing effective clinical protocols.…”
Section: Secondary Phasementioning
confidence: 99%
“…In addition to the nutritional deficit, other way to obtain cells that are not under regular metabolic or physiological condition is to work with cells growing in conditions of hyperglycemia or those collected from patients with diabetes or animals experimentally diabetic, or even cells collected from areas of healing, or with cultures that have already reached the confluence and that in these cases present contact inhibition and lessening of its metabolic potential [16]. Recently, Góralczyk et al [17] have demonstrated that endothelial cells irradiated at 830 nm secrete less inflammatory mediators, such as TNF-α, and present enhanced cell proliferation when cultured under hyperglycemia conditions.…”
Section: Pbmt Effect On Different Types Of Cellsmentioning
confidence: 99%
“…The beam excites the relevant channels and activities, regulates the function of organs, and promotes metabolism. Recently, several papers have reported that the decisive factor in the efficacy of LA is the applied dosage [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%